Sentidos e significados produzidos pelo professor sobre o ensino fundamental de nove anos - Capuchinho, Alessandra de Oliveira (2008)
This work searched to apprehend the sensible meanings and given by the professor about the basic education of nine years, at a moment where magnifying starts to be implanted in all domestic territory. Until then, only some Brazilian cities had implanted the basic education of nine years. The used theoretical perspective to the long of the research has left of the estimated ones of the Partner-historical Psychology, whose methodology referential understands the man as to be historical, constituted in and of the social relations. The qualitative boarding was used in this research, having as instruments of collection of data a closed questionnaire for characterization of the participant citizens of the research and interviews half-structuralized with professors of the first series of the basic education of the public school of a city of the Great Sao Paulo. The analysis process occurred by means of the join up of daily pay-pointers, which had been organized in pointers, which, after articulated and systemize had evidenced six groups of significance: Infantile education, Experience with the Literacy, Basic Education of Nine Years, and Action of the Professor, Parents and Pupils and the Vision of the Professor about Basic Education of Nine Years. The analysis of the data demonstrated that the sensible meanings and produced by the professors on the basic education of nine years guide their pedagogical practical. Therefore, it is necessary that changes, as of basic education, are gestates collectively, with the participation of all the involved actors. So that the real necessities of the children are guaranteed, it s necessary that offers to the professor the necessary conditions for the teaching exercise